2016
DOI: 10.1038/srep38916
|View full text |Cite
|
Sign up to set email alerts
|

A novel approach to quantify different iron forms in ex-vivo human brain tissue

Abstract: We propose a novel combination of methods to study the physical properties of ferric ions and iron-oxide nanoparticles in post-mortem human brain, based on the combination of Electron Paramagnetic Resonance (EPR) and SQUID magnetometry. By means of EPR, we derive the concentration of the low molecular weight iron pool, as well as the product of its electron spin relaxation times. Additionally, by SQUID magnetometry we identify iron mineralization products ascribable to a magnetite/maghemite phase and a ferrihy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 71 publications
(92 reference statements)
4
49
0
1
Order By: Relevance
“…However, the size of the iron particles and/or their chemical moiety seems to be unchanged, as coercivity and remanent magnetisation remained unaltered. SQUID magnetometry is a novel approach to quantify different iron forms in biological samples with high sensitivity that might provide new information for the understanding of the pathomechanisms of various diseased states as described previously [40,43]. The relative reduction of iron-containing compounds in Epi-treated vs. control rats in this study might be related to the inhibition of iron absorption in the enterocytes by Epi or its metabolites [56].…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…However, the size of the iron particles and/or their chemical moiety seems to be unchanged, as coercivity and remanent magnetisation remained unaltered. SQUID magnetometry is a novel approach to quantify different iron forms in biological samples with high sensitivity that might provide new information for the understanding of the pathomechanisms of various diseased states as described previously [40,43]. The relative reduction of iron-containing compounds in Epi-treated vs. control rats in this study might be related to the inhibition of iron absorption in the enterocytes by Epi or its metabolites [56].…”
Section: Discussionmentioning
confidence: 58%
“…A Quantum Design MPMS-XL 7AC (SQUID) magnetometer with a reciprocating sample operation option (with differential sensitivity of 10 −11 Am 2 up to 0.25 T and 10 −10 Am 2 up to 7 T) was used to compare the relative content of iron and iron-containing compounds in the blood samples. The advantage of this method is its ability to determine all of the iron forms in a small sample of biological material, with high sensitivity [40][41][42].…”
Section: Determination Of the Relative Iron Content In Bloodmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, magnetometry requires minimal sample preparation, contrary to TEM, thus lowering the risk of sample contamination. The observation that IRM curves obtained from human material saturate at magnetic fields of 300 mT or lower, and at temperatures between 50 K and 293 K 2,3,13,17,19,20 , and the occasional observation of the Verwey transition 3,19 , support the use of magnetometry techniques to detect and potentially quantify magnetite and/or oxidised magnetite, i.e. maghemite, nanoparticles in post-mortem or ex-vivo human samples.…”
Section: Introductionmentioning
confidence: 80%
“…The concentrations are in the range 0.2-12 µg of magnetic material per gram of dry tissue, and the diameters are spread between 10-150 nm. Moreover, in December 2016, the authors of [6] have shown that a combination of two specific methods offers a unique possibility to study and properly characterize the iron accumulation in the human brain. They also formulated the observation that magnetic moments of magnetite/maghemite nanoparticles are blocked for sizes exceeding 40-50 nm at the room temperature.…”
Section: Magnetic Properties Of Brain Tissue and The Approach Of Elecmentioning
confidence: 99%